To what extent do sea-ice algae affect the modelled transmittance of photosynthetically active radiation (PAR) to the ice-ocean interface? - Benjamin H. Redmond Roche; Martin D. King (Journal of Glaciology)
Photosynthetically active radiation (PAR) at the ice-ocean interface is critical for primary production. The value of PAR is affected by the thickness of snow and sea ice, with additional absorbers (e.g. algae) further attenuating PAR. Sea-ice algae exhibit a substantial geo-temporal variance in column-integrated concentration (0–500 mg chl-a m−2) and are typically present within the bottom 0.01–0.2 m of sea ice. PAR transmittance is affected by algae concentrations and vertical thicknesses of ice algal layers. Small column-integrated concentrations of chl-a (~<10 mg chl-a m−2) have a negligible effect on the value of PAR transmittance, and large column-integrated concentrations of chl-a (~>10 mg chl-a m−2) can significantly reduce the value of PAR transmittance. Large column-integrated concentrations of chl-a need consideration when calculating PAR transmittance in areas of high sea-ice algae biomass (e.g. the ‘interior’ shelves of the Arctic Ocean, the Canadian Arctic and Antarctica).